Dampak ekonomi digital dan tingkat inflasi terhadap pertumbuhan sektor ekonomi di indonesia - Masfiatun, Masfiatun; M Supriyadi, M Supriyadi; Nahdila, Muhammad (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
This research is motivated by the condition of economic growth in Indonesia, which has slowed down after being affected by COVID-19. The government's imposition of social restrictions has disrupted the economic cycle, particularly distribution and consumption. This condition became the basis for the emergence of digitalization in the economic sector. Besides the need for innovation, it is also important to maintain price stability or avoid inflation. The purpose of this study is to determine the impact of the digital economy and the inflation rate on growth in the economic sector in Indonesia. The method used in this study is a time series method using historical data from 2010–2020. The results of this study indicate that the digital economy variable has a significant positive effect on economic growth for the primary and secondary sectors, while the inflation variable has no significant effect.